The Dutch Enemy, Count Duke of Olivares and the Service of the Vassals in the Recovery of Bahia of Brazil - Rivero Rodríguez, Manuel (Eikón / Imago, 2020)
This paper proposes the reading of “The Recovery of San Salvador de Bahía”, proposing a correspondence between the historical moment of 1625 and that of 1633, when the paintings of the Hall of the Kingdoms were commissioned. The event had a fundamental role in the construction of a project of Monarchy that needed a common enemy to build solidarity between the kingdoms. With the unity of the crowns of Portugal and Castile not well established, Olivares would use the campaigns of Brazil to exalt this necessary cooperation, not only for the common defence, but also to develop the project of the Catholic or Universal Monarchy.